Insect-fungal associations : ecology and evolution - Vega, Fernando E.; Blackwell, Meredith (Oxford University Press, 2005)
There is an increasing interest in using fungi as bio control agents for insect pests in agricultural systems, and also a growing interest in the basic biology of insect-fungal associations from the perspective of parasitism, symbiosis and infection. This title covers topics in this field, incorporating new molecular techniques wherever possible.